2019
DOI: 10.1161/hypertensionaha.119.13027
|View full text |Cite
|
Sign up to set email alerts
|

Association of Blood Pressure Level With Left Ventricular Mass in Adolescents

Abstract: Hypertension is associated with left ventricular hypertrophy (LVH), a risk factor for cardiovascular events. Since cardiovascular events in youth are rare, hypertension has historically been defined by the 95th percentile of the normal blood pressure (BP) distribution in healthy children. The optimal BP percentile associated with LVH in youth is unknown. We aimed to determine the association of systolic BP (SBP) percentile, independent of obesity, on left ventricular mass index (LVMI), and to estimate which SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 43 publications
5
66
0
1
Order By: Relevance
“…However, there are different definitions for LVH (1,2,12,(17)(18)(19). In addition, LVH is not only affected by BP but also by age, sex, height, race, BMI, fat mass, and lean mass (20)(21)(22)(23). In our study, regression analysis revealed that the main predictors of LVMI z score were male sex, BMI z score, SBP, and PWV z score, explaining about 33.6% in concordance with literature.…”
Section: Discussionsupporting
confidence: 88%
“…However, there are different definitions for LVH (1,2,12,(17)(18)(19). In addition, LVH is not only affected by BP but also by age, sex, height, race, BMI, fat mass, and lean mass (20)(21)(22)(23). In our study, regression analysis revealed that the main predictors of LVMI z score were male sex, BMI z score, SBP, and PWV z score, explaining about 33.6% in concordance with literature.…”
Section: Discussionsupporting
confidence: 88%
“…In a cross-sectional study conducted in the USA, Flynn and Alderman reported that prehypertensive children were younger, their BMI values were lower, and the prevalence of obesity among them was 20%, while hypertensive children were older, their BMI was within the range of overweight, and the prevalence of obesity among them was 50% [27]. In a recent study, it was observed that BMI values increased with an increase in blood pressure status from below the 80th percentile, 80-90 to the > 90th percentile [28]. However, average BMI in adolescents with blood pressure above the 90th percentile was at the 86th percentile.…”
Section: Body Compositionmentioning
confidence: 98%
“…The tendency for elevated serum uric acid levels, even in the upper normal range (> 5.5 mg/dl), was found to be typical for adolescents with PH, and distinguished them from those with white-coat hypertension and secondary hypertension [47]. In a recent report from the SHIP-AHOY study, it was stated that the mean serum uric acid concentrations increased from 5.3 to 5.9 mg/dl with increasing blood pressure values from below the 80th to above the 90th percentile [28]. Moreover, Feig et al reported that allopurinol used in adolescents with PH and serum uric acid levels above 6 mg/dl lowered both the level of uric acid and blood pressure [48].…”
Section: Hyperuricaemia and Primary Hypertensionmentioning
confidence: 99%
“…Retinal vessel diameters are valid microvascular biomarkers shown to be associated with a higher risk of hypertension and obesity, incidence of stroke and myocardial infarction as well as higher cardiovascular mortality in adults (17,18). With elevated blood pressure not being benign in children and previously linked to target organ damage including increased carotid intima-media thickness (19) and left ventricular mass (20), this study will additionally explore the links with the retinal microvasculature as target organ damage marker in South African children. A previous study indicated that childhood obesity, high blood pressure, and physical inactivity were associated with retinal microvascular abnormalities, suggesting retinal vessel imaging as promising biomarkers for early risk stratification in children (21).…”
Section: Introductionmentioning
confidence: 99%